If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying U = F(b + A) Reorder the terms: U = F(A + b) U = (A * F + b * F) U = (AF + bF) Solving U = AF + bF Solving for variable 'U'. Move all terms containing U to the left, all other terms to the right. Simplifying U = AF + bF
| (1/2)x+(3/2)x=16 | | n/10-2.5=7.5 | | 98=2w+1+w | | 840=120+45n | | -x^4+3x^2-2=0 | | y=.5x-2 | | -17=a/5-8 | | 7x-(6x+5)=3 | | (x/1)=234 | | 2x^2-3xy-35y^2=0 | | x+2x+5x=40 | | j+20= | | 3(2+c)=2(c-1) | | 2-4t+5=15 | | 14x+2y=45 | | 3y-4x=31 | | -x^3-3x^2+4x+12=0 | | (76.5+x)+2x=180 | | 2y+3=3(y-7) | | 4m-8= | | (3x+1)/5=5 | | 20x-5=7+16 | | 2(3x+1)=9x | | 2x-(3x+2)=-7 | | n+(-7)-n= | | g(t)=.75t+3 | | 1.06y-3=8.62 | | 1-2c+12=-3+12-20 | | 25x+70-5x=-20.9 | | 2(3-5x)+2(x-7)=ax+b | | 12-(-u)=19 | | 7b-(2b+7)= |